In vitro study on potential pharmacological activity of curcumin analogues and their copper complexes. (23rd September 2016) - Ferrari, Erika; Benassi, Rois; Saladini, Monica; Orteca, Giulia; Gazova, Zuzana; Siposova, Katarina
Abstract : Curcumin and its derivatives have attracted great interest in the prevention and treatment of Alzheimer's disease, thanks both to the ability to hinder the formation of amyloid‐beta (Aβ) aggregates and the ability to bind Cu (II) ion. In this article, we explore the ability of curcumin derivatives of K2T series to affect amyloid Aβ1–40 aggregation. These derivatives were obtained by introducing the t ‐butyl ester group through a methylenic spacer on the central carbon atom of the β‐diketo moiety of curcumin frame. The studied curcuminoids were demonstrated to inhibit Aβ1–40 fibrillization at substoichiometric concentrations with IC50 value near that of curcumin. In addition, the antioxidant properties and DNA interaction of their Cu(II) complexes is evaluated. The structure of Cu(II)‐K2T31 complex is also proposed on the basis of DFT calculation. Abstract : Curcumin analogues K2T demonstrated to inhibit Aβ1–40 fibrillization. K2T compounds act as copper(II) chelating agents reducing the free metal damage. K2T‐Cu(II) complexes behave as DNA groove binders.